Investigation of equid paleodiet from Schöningen 13 II-4 through dental wear and isotopic analyses: Archaeological implications. Issue 89 (December 2015) - Rivals, Florent; Julien, Marie-Anne; Kuitems, Margot; Van Kolfschoten, Thijs; Serangeli, Jordi; Drucker, Dorothée G.; Bocherens, Hervé; Conard, Nicholas J.
Abstract: The paleodietary traits of the equid population from Schöningen 13 II-4 were investigated through tooth mesowear and microwear analyses, as well as stable isotopic analyses. The mesowear pattern observed on the upper teeth indicates a low abrasion diet with a significant amount of browse in the diet of the horses. The tooth microwear analysis and the isotopic data confirm that the horses from Schöningen 13 II-4 were mixed feeders, like many populations from other Pleistocene localities in Northern and Eastern Europe. Microwear also provides information on seasonal changes in the diet of the horses and offers the possibility to test hypotheses about the presence of one or several horse populations. Our analysis determined that the assemblage of horse remains from Schöningen 13 II-4 resulted from multiple accumulation events, which took place at different periods of time.